If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2y + 4y + -2x = 0 Reorder the terms: 3x + -2x + 2y + 4y = 0 Combine like terms: 3x + -2x = 1x 1x + 2y + 4y = 0 Combine like terms: 2y + 4y = 6y 1x + 6y = 0 Solving 1x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 1x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 1x + 0 = 0 + -6y 1x = 0 + -6y Remove the zero: 1x = -6y Divide each side by '1'. x = -6y Simplifying x = -6y
| 0=1600x-x^2 | | 4y=-6-14 | | 0=-1600x-x^2 | | 6(2+7x)=12 | | 3x+9y=-108 | | 8n+13=7(n+10) | | 8x-9=4x | | 3(2X+2)-4(3X+2)=5X+20 | | (6x-3)=(4x+7) | | 2x=(360+2) | | (6)*(3x+2)=(6)*(5x-10) | | R(6x-3)=(4x+7) | | 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 |